Catastrophes caused by corrosion - Petrović, Zoran C. (Vojnotehnički glasnik / Military Technical Courier, 2016)
For many years, huge attention has been paid to the problem of corrosion damage and destruction of metallic materials. Experience shows that failures due to corrosion problems are very important, and statistics at the world level shows that the damage resulting from the effects of various forms of corrosion is substantial and that, for example, in industrialized countries it reaches 4-5% of national incomes. Significant funds are determined annually for the prevention and control of corrosion. In the case of ignoring the problem of corrosion, in some cases the penalty is financial, whereas in other cases it is the loss of human lives. This review presents several cases of failures in engineering structures and installations of catastrophic proportions, where corrosion was responsible for the occurrence of failures and the loss of hundreds of lives.
Keywords: catastrophe; failure; corrosion; corrosion pit; pesticide; explosion; pipeline; helicopter; aircraft